Epistimologi Sebagai Landasan Metodologi Ilmiah untuk Pengembangan Teori Baru Bidang Manajemen Pendidikan Islam - S, Rinny; Rahmawati, Aulia; Irawadi, Hermen; Saputra , Septia Irnanda; Jamilus, Jamilus (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to identify and analyze the relationship between Islamic epistemology and scientific methodology in the context of Islamic education. This study uses a literature review methodology, data collection through in-depth examination of relevant and credible sources, such as scientific journals, academic books, research articles, and other related documents that support the research topic. The data collection technique involves systematically filtering the literature based on specific criteria, including topic relevance, source credibility, and year of publication, to ensure the accuracy and timeliness of the data. This analytical process helps in developing a comprehensive conceptual framework and building strong arguments for interpreting the research findings. The results of the analysis show that epistemology plays an important role in the development of new theories in the field of Islamic education management. Islamic epistemology, which combines revelation and reason, provides a solid foundation for a scientific methodology that is in line with Islamic values. In addition, an epistemological approach can also help to address the challenges in Islamic education management in the modern era by providing an ethical and adaptive framework